Sociological study about the teen pregnancy in Ucayali Region: 2000-2012 - Díaz Encinas, Alida Isidora (2015)
The national teen pregnancy indicators still are in alarming numbers, the «Sociological study about the teen pregnancy in Ucayali region: 2000-2012» analyzes this phenomenon in the mentioned region. Taking as a point of stadistical reference the Encuesta Demográfica de Salud (ENDES) we analyze the evolution of the mentioned indicators. Also the fieldwork realized in the establishments of the MINSA in Pucallpa’s city, it allows us to get conclusions about the life experiences of the pregnant teenagers.